Behaviors towards purchasing goods by foreign tourists in LuangPrabang City - SIOUDOMPHAN, Soutthavone; KINGSADA, Youtthasack; THAMMAVONG, Vanhxay; LAYASAENG , Somyoth; OUNPHOUVONG, Stamy (Souphanouvong University Journal Multidisciplinary Research and Development, 2021)
The paper aims to study 1) foreigner behaviors in buying handicraft products in LuangPrabang. 2) Market mix that determine the foreigners’ decision in buying the products. 3) Suggestions by buyers on what product development can be made. This result is surely useful for entrepreneurs and local product producers and it is also useful for policy makers in order to improve and develop producers’ skill as well as the products. The simple random sampling is used in questionnaire dispersal. Descriptive statistics is used as well as Chi-square. The result shows that most product buyers are males who aged from 20-29. Their monthly incomes are between 1.000 – 10.000. They are mainly from China, US, Vietnam, Thailand, France, Australia and Japan. The products bought by them included are scarf, Lao silk suit and Sa paper, and mostly for souvenir. The market mix plays medium role in the customer decision making in buying the products. In terms of respondent information variable, can be found that the respondent gender has a link to buying purpose but it has no link to the buying frequency and no link to buying manner with the important statistic value of 0.05. Age, status, education level, occupation, nationality and the number of times visiting LuangPrabang has a link to all buying behaviors with the importance statistic value of 0.05. Surprisingly, the respondent income doesn’t have any link to their buying behavior. In terms of market mix variable, the result can be seen that products, distribution and market promotion have a link to buying behavior in the important statistic value of 0.05. Interestingly, product price doesn’t have any link to the buying behavior with the important value of 0.05.